Pendekatan Model Komunikasi, Partisipasi Kelompok dalam Adopsi Inovasi Agribisnis Ternak Kambing PE di Girikerto - Sleman Daerah Istimewa Yogyakarta - Hano Hanafi; Soemardjo Soemardjo; Amirudin Saleh; Ida Yuhana (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2004)
The essence of the participatory development is to encourage society to behave independently in all fields. This mean that it is need an interaction and interdependency ofall the parties involved in the development, including government, society and private institutions, to mobilise the energy and the sources given in the society. This research was conducted to support the implementation of innovation of PE sheep agribusiness in the group level in Girikerto, Sleman Regency. This research aimed at knowing the effective group communication model in the adoption and innovation of the PE sheep agribusiness, and to knowing the level of participation of the groups' members in the adoption and innovation of the PE sheep agribusiness.This research was conducted in Girikerto village, Turi Sub-regency, Sleman Regency of Yogyakarta Province in the period of August – November 2001. The analysis units in the research were individual members of breeder group of PE sheep in Girikerto village. The studied groups was set